PESANTREN EDUCATION AND ULAMA REGENERATION - Subri Hasan (Proceeding International Seminar of Islamic Studies, 2021)
Pesantren and ulama are inseparable like the two sides of a coin. So when mentioning pesantren, the meaning of Islam and Indonesia has been linked, between Islamic education and ulama and between religion and the people. Therefore, it is not an exaggeration that pesantren has become the center of da'wah, syi'ar and Indonesian Islamic education as a place for the reproduction and regeneration of Indonesian ulama.Some of the literacy written by Martin Van Bruinessen, Manfred Ziemek, Zamakhsyari Dhofier, Nurholis Majid, Abdurrahman Wahid, M. Dawam Raharjo, and Azyumardi Azra seems sufficient to be a reference for this paper. The important point of this study is that pesantren, with their distinctive characteristic, mastery of the yellow book or Islamic studies, are the main standards that scholars must have. So that the majority of Indonesian ulama were born from the womb of the pesantren as the first home for their Islamic education and knowledge. So ulama who are "not pesantren" are not sufficient to "bear" themselves as ulama. Ulama and pesantren are like books with their writings (contents).     Keywords: Pesantren, Regeneration, Ulama